The Impact of Trade Openness and Financial Openness on Information Efficiency of Five ASEAN Countries’ Stock Market 2000-2014 - Nugroho, Setyo; Danarsari, Dwi Nastiti (UI Scholars Hub, 2019)
This paper investigates the impact of trade openness and financial openness towards informationefficiency of the ASEAN countries’ stock market. The sample consists of the five most developedstock markets in the ASEAN region – Indonesia, Malaysia, the Philippines, Singapore, and Thailand, covering research period of 2000-2014. This study employs panel data analysis in the model. The result suggests that, when Singapore is excluded from the sample, de facto trade openness has a negative impact on information efficiency, while de facto financial openness has a positive impact on information efficiency. De jure measure is shown to have no significant impact on information efficiency.